The effects of applying cellulase and laccase on fermentation quality and microbial community in mixed silage containing corn stover and wet brewer’s grains - Li, Li; Xie, Xiangxue; Zhao, Guoqiang; He, Jiajun; Zhang, Yongliang (Frontiers in Plant Science, 2024)
The purpose of this experiment was to explore the effect of adding cellulase and laccase on fermentation quality and microbial community in mixed silage of corn stover and wet brewer's grains. Try to a new approach for the proper preservation and utilization of the agro-industrial by-products (corn stover and wet brewer's grains).The experiment was divided into four groups: CK (control), C (cellulase, 120 U/g fresh matter [FM]), L (laccase, 50 U/g FM), CL (cellulase 120 U/g FW and laccase 50 U/g FM), and the chemical composition, fermentation quality, microbial population and microbial community in mixed silage of corn stover and wet brewer's grains after 30 day's fermentation were determined.Results: Compared to control, the addition of cellulase significantly increased crude protein (CP), water-soluble carbohydrate (WSC), lactic acid bacteria (LAB) counts, while significantly decreased the neutral detergent fiber (NDF), acid detergent fiber (ADF) content (P < 0.05). Adding laccase significantly decreased the acid detergent lignin (ADL) content (P < 0.05). Combined application of cellulase and laccase significantly increased the CP, WSC content and LAB counts, while significantly decreased pH value, NDF, ADF and ADL content (P < 0.05), thereby improving fermentation quality. In addition, the application of cellulase and laccase increased the abundance of Firmicutes and LAB genera, and decreased microbial diversity level of the sample.The combined application of cellulase and laccase further improved fermentation quality and microbial community in mixed silage of corn stover and wet brewer's grains.